The Maqasid Methodology in Contemporary Interpretation: An Applied Study: Metodologi Maqasid dalam Penafsiran Kontemporer: Sebuah Studi Terapan - Otaiwi, Faris Fadheel (Indonesian Journal on Health Science and Medicine, 2025)
The present research is aimed at considering the approach to the methodology of maqasid-based interpretation in modern exegesis based on models that use the objectives of Islamic law as a tool for the interpretation of the Qur'anic text. The research reveals the theoretical grounds of this approach, the motives for its development in modernity, and the calculation of its practical usage, paying primary attention to the works of Shi'a Imami exegetes while using certain works from other interpretive schools as support. The research uses descriptive, analytical, and critical means to appraise the interpretative texts and the degree of adherence to principles and guidelines of exegesis. The study concludes that the maqasid approach has contributed remarkably to the contemporary Qur'anic interpretation, but only insofar as it is used strictly within the boundaries of scholarly and legal criteria. The research suggests the further refinement of this methodology in order to reconcile Islamic law goals with textual limitations of the Qur'an. Highlights: Purpose-Driven Interpretation: Maqasid methodology emphasizes understanding Qur'anic texts by linking them to the higher objectives of Shari'ah—justice, mercy, and public interest Imami Contribution: Imami scholars apply this method uniquely by integrating authoritative narrations from Ahl al-Bayt with Qur'anic analysis, ensuring a balance between text and contextual realities Scholarly Models: Ibn Ashour and Farid al-Ansari exemplify modern applications—Ashour through legal objectives and text integration; Ansari through educational and spiritual reforms via Qur'anic councils Keywords: Maqasid, Interpretation, Imami, Objectives, Methodology